2021
DOI: 10.1186/s12887-021-02523-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different detection methods for Mycoplasma pneumoniae infection in children with community-acquired pneumonia

Abstract: Background Due to the lack of a sensitive, specific and rapid detection method, aetiological diagnosis of pneumonia caused by Mycoplasma pneumoniae (M. pneumoniae, MP) is a constantly challenging issue. This retrospective study aimed to compare the diagnostic methods for Mycoplasma pneumoniae in children and evaluate their values. Methods From November 2018 to June 2019, 830 children with community-acquired pneumonia were selected from the Departme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
3
20
0
4
Order By: Relevance
“…For the detection of M. pneumoniae , it has been reported that combined detection methods can improve the specificity and sensitivity of diagnosis and reduce false-negative and false-positive rates. M. pneumoniae cannot be reliably diagnosed using only a single test ( Loens and Ieven, 2016 ; Tang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of M. pneumoniae , it has been reported that combined detection methods can improve the specificity and sensitivity of diagnosis and reduce false-negative and false-positive rates. M. pneumoniae cannot be reliably diagnosed using only a single test ( Loens and Ieven, 2016 ; Tang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given antibodies against M. pneumoniae could be affected by co-infection and patients' immune state [31,32], and results of PCR could be affected by antibiotics, techniques, and asymptomatic carriage [33,34], a combination of multiplex-PCR and serology helps to reduce each other's 'false positive' and 'false negative' rates and was considered to have the highest specificity and sensitivity [31]. However, paired serum samples are difficult to obtain in pediatric, and study demonstrated that titer of 1:160 had a high sensitivity and the highest Youden index and Kappa value using PCR as the standard indicating that it was conducive to screening for M. pneumoniae infection [35], coupled with that multiplex-PCR is expensive, therefore, our retrospective study relied mainly on clinical manifestations of respiratory infection combined with a single antibody titer ≥ 1:160. Another, we have to make longer observation and get more systematic surveillance data for better understanding of the epidemiology of M. pneumoniae in COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has some limitations. First, it is time-consuming (24-72 h) and the second is low bacterial growth in people who have received antibiotics [ 11 , 12 ]. Hence, using molecular techniques such as polymerase chain reaction (PCR) that are rapid and sensitive, can improve the speed and accuracy of detection of CAP pathogens [ 13 ].…”
Section: Introductionmentioning
confidence: 99%